Pemanfaatan Media Flashcard Melalui Belajar Kelompok pada Mata Pelajaran Ekonomi Syariah - Fitri Kurnia (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
A study conducted on SMK Bayt Al- Hikmah Pasuruan's 10th grade students found that the majority of the teaching strategies employed in Islamic Religious Education (PAI) classes were lecture-based, which resulted in a lack of variety in the approaches used. This resulted from the PAI teachers' lack of experience with teaching techniques and their foreign graduation backgrounds.Furthermore, education specialist Mr. Munif Chatib's